3D-model and 3D-modeling in industrial design - S.V. Verhunov (Academy of Cognitive and Natural Sciences, 2009)
In the article undertake the attempt to formulate the definition of 3D-model and process of 3D-modeling in industrial design, cons hit definitive aspects of this conception from the position of industrial designer and todays production process.